Earning Management Analysis: The Role of Firm Size, Leverage, Managerial Ownership and Profitability - Safarida, Nanda; Lili Irawati; Safwan Kamal (IAIN Langsa, 2023)
Purpose: This study aims to determine the effect of firm size, leverage, managerial ownership, and profitability on earning management in a convenience goods company, PT. Tiga Pilar Sejahtera Food Tbk, wich is listed on the Indonesian stock exchange under the name AISA. Method: Secondary data are collected through the company’s financial statement from 2006 to 2020. The data were collected from the Indonesian Capital Market Directory (ICMD) and the Indonesian stock exchange websites. The quantitative approach was used to analyze the data. Then, the data were regressed by Ordinary Least Square estimation using Eview 12 software. Findings: Results revealed that firm size, managerial ownership, and profitability have no significance influence on earning management. However, leverage partially has a negative and significant effect on the earnings management. Meanwhile, firm size, leverage, managerial ownership, and profitability simultaneously influence earnings management of PT. Tiga Pilar Sejahtera Food Tbk significantly from 2006 to 2020 period. Research limitation: This research only uses some of the determinants of earnings management from many other factors that also have a contribution such as institutional ownership, board of commissioners, auditor reputation, etc. In addition, the use of several research objects in the form of companies engaged in the same business sector is also recommended for further research in order to obtain a more comprehensive and representative view. Practical Implication: This research has implications for the company's management considerations in making decisions to carry out earnings management. This form of intervention is ideal as long as it is carried out in accordance with accounting principles. This must be ensured so that the company's economic picture remains visible and risk management can still be carried out.